Pengaruh Digital Marketing dan Penggunaan Digital Payment Terhadap Keputusan Pembelian Kopi Espresso Based - Muhammad Faqih Arrizik; Suparno Suparno; Ayatulloh Michael Musyaffi (Universitas 45 Surabaya, 2024)
This quantitative research was conducted in the DKI Jakarta area and focuses on how digital marketing and the use of digital payments influence customers' decisions to buy espresso coffee at Kopi Tuku. The population of this research is Generation Z customers of Kopi Tuku in Jakarta, aged between 17 and 27 years. To measure the population, a Likert scale is used. This study used a purposive sampling method with 264 subjects surveyed. The research analysis method is the Structural Equation Model (SEM). The research results show that the use of digital marketing and digital payments significantly influences consumers' decisions to buy something.